1983
DOI: 10.1007/bf02581268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salicylate poisoning on insulin secretion. Studies on its mechanism of action

Abstract: Sodium salicylate poisoning increased glucose-induced insulin secretion by slices of rat pancreas. The alpha adrenergic blocker phentolamine, but not salicylate poisoning, overcame the inhibitory effect of epinephrine on insulin secretion. Theophylline (5, 10 and 15 mM) significantly increased the insulin secretion induced by 11 mM glucose. The highest insulin response was obtained when theophylline was used at a 10 mM concentration. However, when pancreas slices from salicylate poisoned rats were used, a 5 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
0
4
1
Order By: Relevance
“…This observation is similar to that described in Brassica species, where indehiscent species show a more lignified endocarp than dehiscent ones 54 . By contrast, our findings are opposed to those reported from histological studies in common bean and soybean, where pod valves of the wild dehiscent lines showed a strong lignified wall fiber layer contrasting with a complete absence of lignin deposition in the indehiscent lines 21 , 26 , 34 , 55 , 56 , 58 .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This observation is similar to that described in Brassica species, where indehiscent species show a more lignified endocarp than dehiscent ones 54 . By contrast, our findings are opposed to those reported from histological studies in common bean and soybean, where pod valves of the wild dehiscent lines showed a strong lignified wall fiber layer contrasting with a complete absence of lignin deposition in the indehiscent lines 21 , 26 , 34 , 55 , 56 , 58 .…”
Section: Discussioncontrasting
confidence: 99%
“…Collectively, these studies suggest that pathways and loci controlling pod dehiscence are broadly conserved across taxa, pointing towards homologous mechanisms underlying dehiscence. However, while a convergent phenotypic evolution was proposed across cereals, which might also have occurred at orthologous loci in closely related legume species, such evidence has not been obtained so far across more distant legume crops 34 . Comparative mapping between P. vulgaris and G. max suggested that the convergent evolution of the indehiscent phenotypes derived from mutations at different genes involved in pod cell wall biosynthesis and lignin deposition 44 , which suggested a more complex pattern in the genetic control of this trait in legumes.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Alloantigen injection, in turn, modified not only the amount but also the pattern of 5.5 mM glucose-induced hormone secretion, substituting a monophasic by a biphasic profile. Incidentally, the change in the insulin secretion pattern caused by the injection of allogeneic lymphocytes, where 5.5 mM glucose is used as stimulus, was similar to that elicited by glibenclamide, sodium salicylate, or theophylline, all substances with previously reported stimulatory effects on cyclic AMP pancreatic levels (22)(23)(24). Although any comment or tentative explanation would be, at'present, only speculative, these results could suggest that the increase in beta cell sensitivity to glucose caused by alloantigen injection might be mediated, at least in part, by an effect on cyclic AMP levels.…”
Section: Resultsmentioning
confidence: 65%